1995
DOI: 10.3109/02713689508999936
|View full text |Cite
|
Sign up to set email alerts
|

Retinal dopamine and lens-induced refractive errors in chicks

Abstract: This study investigated the relationship between retinal dopamine and lens induced refractive errors in chicks by high performance liquid chromatography with ultraviolet detection (HPLC-UV). After two weeks of lens wear, the chick eyes treated with +10D lenses were hyperopic (+8.29 +/- 0.43D), while the eyes treated with -10D lenses were myopic (-11.69 +/- 0.74D). At the same time, in myopic eyes the level of retinal dopamine and its metabolite 3,4-dihydroxy-phenylacetic acid (DOPAC) were reduced compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 21 publications
2
65
0
Order By: Relevance
“…Changes in retinal dopamine are also clearly correlated with form-deprivation myopia (Stone et al, 1989), which can be ameliorated in chicks and monkeys by dopamine agonists (Iuvone et al, 1991). Retinal dopamine may also be correlated with the defocus caused by spectacle lenses (Guo et al, 1995 ;Schaeffel et al, 1995), but the correlation is far from perfect (Boelen et al, 1999 ;Schwahn and Schaeffel, 1997). Finally, glucagonergic amacrine cells show opposite changes in ZENK expression in chick eyes wearing positive and negative spectacle lenses (Fischer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in retinal dopamine are also clearly correlated with form-deprivation myopia (Stone et al, 1989), which can be ameliorated in chicks and monkeys by dopamine agonists (Iuvone et al, 1991). Retinal dopamine may also be correlated with the defocus caused by spectacle lenses (Guo et al, 1995 ;Schaeffel et al, 1995), but the correlation is far from perfect (Boelen et al, 1999 ;Schwahn and Schaeffel, 1997). Finally, glucagonergic amacrine cells show opposite changes in ZENK expression in chick eyes wearing positive and negative spectacle lenses (Fischer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The use of modified translucent occluders demonstrates that retinal dopamine levels inversely correlate with the degree of axial elongation (Stone, Pendrak et al 2006). Retinal dopamine levels exhibit a bidirectional response to retinal blur in chicks, with lens-induced myopia decreasing and hyperopia increasing the levels respectively (Guo, Sivak et al 1995) although this effect is not universally reported (Bartmann, Schaeffel et al 1994). The increase in retinal dopamine associated with the slowing of axial growth in lens-induced hyperopia parallels recovery from form-deprivation myopia in the chick where a similar relationship between dopamine level and axial growth is reported (Pendrak, Nguyen et al 1997).…”
Section: Dopamine Melatonin and Refractive Development 61 Dopaminementioning
confidence: 99%
“…In the negative lens-induced chick myopia model, the defocus on the retina and ciliary nerve played an important role in axiallength elongation and caused a change in refractive error [16] . Changes in retinal concentrations of dopamine [17,18] , glucagon [19,20] , all-trans -retinoic acid ( all-trans -RA) [21][22][23] and vasoactive intestinal polypeptide [24,25] have been associated with ocular growth in both negative lens-induced myopia and form deprivation myopia. However, only glucagon and all-trans -RA changed the concentration in opposite directions when positive and negative lenses were worn.…”
Section: Introductionmentioning
confidence: 99%